Absorption spectra of layered ZnI2 and K2ZnI4 compounds intercalated by СО2 - Yunakova, O.N.; Miloslavsky, V.K.; Kovalenko, E.N.; Makovetsky, E.D. (Institute for Single Crystals, 2009)
The absorption spectra of thin films of ZnI2 and K2ZnI4 layered compounds intercalated with СО2 molecules have been investigated in temperature interval from 90 to 240 K. It is found that the intercalation results in high-frequency shift of exciton bands and their broadening. Considering the structure of ZnI2 and K2ZnI4 crystal lattices, the most probable positions of СО2 molecules in spacings between layers of compounds have been established. It is shown that, in K2ZnI4 compound, unlike ZnI2, there are two position types of intercalant molecules with molecular axes of different orientation relative to the compound crystallographic axes.
Keywords: оптика; кафедра физической оптики; ZnI2; K2ZnI4; слоистые соединения; интеркаляция; спектр поглощения; экситон